2017
DOI: 10.1038/jp.2017.107
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections in neonates are independently associated with longer hospitalizations

Abstract: This is the largest study to date analyzing SSI in neonates. We found that perioperative variables have a more significant impact on SSI than patient factors, suggesting that operation-related characteristics are influencing SSI. Furthermore, neonates with SSI are more likely to have prolonged hospitalizations even after adjusting for patient comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Interestingly, the overall rate of SSI in the neonatal age group in our review is comparable to the rates reported in the older pediatric age group (51, 65, 66). This finding suggests that neonates may be less prone to SSI than it might be expected based on their alleged fragility, as they represent a special population that is thought to be at higher risk for infection due to their immature immune systems (6, 67, 68).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the overall rate of SSI in the neonatal age group in our review is comparable to the rates reported in the older pediatric age group (51, 65, 66). This finding suggests that neonates may be less prone to SSI than it might be expected based on their alleged fragility, as they represent a special population that is thought to be at higher risk for infection due to their immature immune systems (6, 67, 68).…”
Section: Discussionmentioning
confidence: 95%
“…According to literature, SSI leads to delay in wound healing and patient recovery, risk for developing sepsis, and delayed bone union. [4][5][6][7] Despite all the protective measures, infection rate is increasing, thus requiring selection of stringent antibiotics to control the infection. 8,9 To reduce the SSI rate, active safety measures are highly recommended by the World Health Organisation standard guidelines.…”
Section: Surgical Incision Always Carries the Risk Of Developing Surg...mentioning
confidence: 99%
“…Therefore, shortening LOS is a potential way to reduce the pressure and better meet the growing medical needs of T2DM patients with limited resources. Previous studies have focused more on the relationship between LOS and characteristics of patients or disease at individual level, and have ignored the adjustment effects of organizational structure and resource distribution at hospital level [14,20,22]. These efforts cannot effectively reduce LOS caused by factors other than disease and patient characteristics.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, they are susceptible to adverse events after surgery [19]. This is a particular objective fact for diabetes patients [20,37]. Patients with ICD-10 coded complications types E11.1, E11.2, E11.4, E11.5 and other complications CVDs had longer LOS.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation